On‐line extreme learning algorithm based identification and non‐linear model predictive controller for way‐point tracking application of an autonomous underwater vehicle. Issue 3 (13th September 2019) - Rath, Biranchi Narayan; Subudhi, Bidyadhar
Abstract : In most of the surveillance applications of autonomous underwater vehicle (AUV), very often it is intended to follow the desired horizontal way‐points, where some oceanography data need to be collected. In view of this, the motion planning algorithm using way‐points is investigated in this study. The proposed work involves identification of dynamics of AUV and design of adaptive model predictive controllers which includes linear adaptive model predictive controller (LAMPC) and non‐linear adaptive model predictive controller (NAMPC). Owing to the fast convergence rate and robustness property, on‐line sequential extreme learning machine (OS‐ELM) is employed for estimating the dynamics of AUV. To improve the OS‐ELM modelling performance, Jaya optimisation algorithm is applied to optimise the hidden layer parameters. The desired surveillance region is formulated in terms of way‐points using heading angle obtained from desired line‐of‐sight path. Simulations are performed using MATLAB by applying proposed NAMPC, LAMPC and a previously reported optimal controller, namely inverse optimal self‐tuning PID (IOSPID) controller. Subsequently, real‐time experimentation is performed using a prototype AUV in a swimming pool. From the simulation and experimental results, it is observed that the proposed controller exhibit efficient tracking performance in face of actuator constraints as compared to LAMPC and IOSPID controller.